1993
DOI: 10.33584/jnzg.1993.55.2082
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of dryland species on 90 east coast North Island farms

Abstract: A drought pasture demonstration programme was established on the east coast of the North Island, between 1990 and 1992. Dryland pasture species were established on 1500 ha, on 91 farms, to encourage other farmers to use them rather than relying totally on perennial ryegrass. 97% of pastures were established successfully, proving to farmers that dryland pasture species can be established reliably. As well as establishing pastures after cultivation, it was also proven that these species can be reliably e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…All are C 3 species which germinate readily with the onset of the cool season (Hume & Barker 1991; Porter, Lucas & Andrews 1993). There is also close agreement with differences in desiccation tolerance between categories B and C. Category C species are common in grasslands of dry environments (Stewart 1992; Milne, Moloney & Smith 1993) whereas category B species prefer moist habitats (Langer 1973; Chapman et al . 1986).…”
Section: Germination Response To Warm Temperature Pulsesmentioning
confidence: 54%
“…All are C 3 species which germinate readily with the onset of the cool season (Hume & Barker 1991; Porter, Lucas & Andrews 1993). There is also close agreement with differences in desiccation tolerance between categories B and C. Category C species are common in grasslands of dry environments (Stewart 1992; Milne, Moloney & Smith 1993) whereas category B species prefer moist habitats (Langer 1973; Chapman et al . 1986).…”
Section: Germination Response To Warm Temperature Pulsesmentioning
confidence: 54%
“…The 106 paddocks measured in this survey were sown as part of the 1988/89 South Island Drought Recovery Programme (Milne & Fraser 1990) or the 1990/91 North Island Recovery Programme (Milne et al 1993). A total of 73 properties (47 South Island, 26 North Island) were represented with 1-3 paddocks per property.…”
Section: Methodsmentioning
confidence: 99%
“…Experience has shown that in most North Island regions, Wana cocksfoot does not offer this opportunity. Milne et al (1993). Smith et al (1993) both reported Kara to be less aggressive relative to Wana in pasture mixtures sown in the North Island East Coast Pasture Demonstration Programme.…”
Section: Kara Cocksfootmentioning
confidence: 99%
“…In a large number of these mixtures, farmers, researchers and advisors have observed that Wana has become the dominant grass species after the second and third year (Korte et al 1992;Smith et al 1993;Milne et al 1993). The results from trial 1 (Table 2) are typical of how Wana's aggressive nature can restrict important contributions from higher quality companion species such as tall fescue and white clover.…”
Section: Wana Cocksfootmentioning
confidence: 99%